Extracellular Vesicle Lipids and Their Role in Delivery - Austin Brent; Paniz Shirmast; Nigel A. J. McMillan (Journal of Extracellular Biology, 2025)
ABSTRACT Small extracellular vesicles (sEVs) possess many advantageous characteristics which highlight their potential as nanocarriers for biomedical applications, including the ability to cross the blood brain barrier, improved biocompatibility and exhibit tissue tropism. Despite this potential, the clinical translation of sEVs has been hindered by a variety of factors and lipid nanoparticles (LNPs) remain as the gold standard for nanocarriers, indicating a knowledge gap which could unlock the potential of sEVs. A growing body of research suggests that the lipid profile, rather than the proteome, of sEVs may be contributing to these beneficial characteristics much more than previously thought. This review highlights and discusses the current state of the field in terms of lipid composition between sEVs originating from various cell sources and the roles which the different lipids play in the function of sEVs as natural nanocarriers within the body. We also discuss the potential of various EV‐mimetics and synthetic EVs (synEVs) in terms of clinical translation which may provide a means to allow wider therapeutic adoption of EVs.